Worlds and individuals, possible and otherwise - Yagisawa, Takashi (Oxford : Oxford University Press, 2010)
Takashi Yagisawa argues for a new version of modal realism, the view that non-actual possible worlds and individuals are as real as the actual ones. He asserts that the notion of reality is primitive, existence is a relation between a thing and a domain and ordinary objects are extended in spatial, temporal, and modal dimensions.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Modality (Logic); Realism; Plurality of worlds; Possibility